The influence of financial innovation on the performance of banks in Tunisia: Insights from a survey - Ben Mahmoud, Arij; Khalifa, Jihène (International journal of economic perspectives, 2024)
This study was conducted to analyze the impact of financial innovation on bank performance, motivated by the low profitability and subsequent closures of certain banks due to the COVID-19 pandemic. Determinants of financial innovation were identified and included in the analysis to understand their relationship with bank profitability. Financial innovation encompasses the creation of new financial instruments, the adoption of new financial technologies, and the development of financial institutions and markets. An empirical study was carried out with a sample of 150 individuals at Banque Nationale Agricole Tunisia using a survey. The results indicate that Banque Nationale Agricole has taken significant steps to adopt new financial products and services, thereby strengthening its capital base and becoming a source of funding for research and development.